Nitrogen Budget of South Korea from 2015 to 2019 Including Gaseous Nitrogen Oxides - Hyun-Kyung Kim; Seong Min Park; Jae-Woo Park (대한환경공학회지, 2023)
Objectives The study was aimed to systematically understand the nitrogen budget from 2015 to 2019, and to determine the annual nitrogen balance in South Korea. Methods The nitrogen budget was calculated by classifying into agricultural and livestock, city, and forest areas. The nitrogen input was estimated from deposition, biological fixation, agricultural water, inorganic chemical fertilizer, compost, feedstuff, produced crops, imported grocery, and fuel consumption. The nitrogen output was estimated by considering denitrification, volatilization, ground water runoff, land and crop absorption, sewage disposal, drainage, forest uptake, and nitrogen oxide (NOx) emissions. Results and Discussion The annual nitrogen budget from 2015 to 2019 showed the input as 6,107,449 ton/yr, 6,144,666 ton/yr, 6,245,240 ton/yr, 6,281,552 ton/yr, 5,993,347 ton/yr and the output as 1,346,587 ton/yr, 1,369,119 ton/yr, 1,365,327 ton/yr, 1,378,940 ton/yr, 1,365,994 ton/yr, respectively. The NOx, highly contributing to change in the nitrogen budget, was caused by human activities such as vehicles, business places, and power plants. More than 32% of the total nitrogen budget was caused by NOx in every year. Conclusion The nitrogen budget continued to increase in the 2010s because of the increase in food and fuel consumption by urbanization. However, the nitrogen budget declined in 2019 due to the effort such as emission regulations and the use of alternatives as the awareness of environmental pollution gradually increased. Therefore, the appropriate institution should be established and actively implemented to reduce the nitrogen effectively.